Impact Factors on Subcontractor's Cash Flow Management - Medhat A. Youssef; Ahmed H. Ibrahim; M. El-Sayed El-Badawy Hafez (Civil Engineering Journal, 2023)
Objective: This study aims to define how to maintain and protect the subcontractor firms' cash flow from economic fluctuation through legally sustainable solutions. Methods/Analysis: We conducted a case study in the Eastern Delta Region of Egypt. A questionnaire containing a list of 22 impact factors on subcontractors' cash flow was distributed across multiple subcontractor firms with an 82% response rate. It was designed to explore the factors causing cash flow instability and analyze them using SPSS statistics. Findings: The study finds that inflation, late payments, non-compensation for late payments, poor subcontractor cash flow management, subcontractor firms' inclination to avoid disputes, material price fluctuation, and non-compensation terms, as well as suppliers rejection of payment delays, are the most critical factors of subcontractor cash flow problems. Novelty/Improvement:The study suggests adding three sub-articles to Article 57 in "Tender Law" as legally sustainable solutions to protect and maintain the firm's growth rate from inflation, late payment, and the inclination to avoid disputes. Also, the study recommends that the owner ensure that cash is available before procuring the general contractors, as stated in Egyptian Law 182 of 2018. This study will contribute to establishing a sustainable win-win relationship between subcontractors and general contractors. Doi: 10.28991/CEJ-SP2023-09-08 Full Text: PDF